2021
DOI: 10.2169/internalmedicine.5722-20
|View full text |Cite
|
Sign up to set email alerts
|

Anti-glomerular Basement Membrane Glomerulonephritis During the First Trimester of Pregnancy

Abstract: A 28-year-old woman was admitted during the eighth week of her pregnancy because her clinical course was consistent with rapid progressive glomerulonephritis (RPGN). Anti-glomerular basement membrane antibody (anti-GBM Ab) and MPO-ANCA were positive, and the anti-GBM Ab titer being extremely high. She was treated with hemodialysis, plasma exchange and prednisolone. She survived the illness; however, neither the fetus nor her kidney function could be rescued. She had HLA-DRB1*1502:01, which differs from the DRB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…To our knowledge, this is the frst case of atypical anti-GBM disease in pregnant patients with suspected systemic lupus erythematosus reported in the literature, and to date, there are only approximately ten case reports of anti-GBM antibody glomerulonephritis in pregnant patients [5][6][7][8][9][10], and only two of them are negative against anti-GBM antibodies [8,9]. Al-Harbi et al reported a 30-year-old woman with acute renal failure at 28 weeks of gestation, whose repeat anti-GBM antibody test in a serum sample taken after delivery was positive [8].…”
Section: Discussionmentioning
confidence: 87%
“…To our knowledge, this is the frst case of atypical anti-GBM disease in pregnant patients with suspected systemic lupus erythematosus reported in the literature, and to date, there are only approximately ten case reports of anti-GBM antibody glomerulonephritis in pregnant patients [5][6][7][8][9][10], and only two of them are negative against anti-GBM antibodies [8,9]. Al-Harbi et al reported a 30-year-old woman with acute renal failure at 28 weeks of gestation, whose repeat anti-GBM antibody test in a serum sample taken after delivery was positive [8].…”
Section: Discussionmentioning
confidence: 87%
“…This condition raised the question of whether there was any association between the pregnancy and anti-GBM disease. Kai et al [ 16 ] reported a case of a 28-year-old female who was diagnosed with anti-GBM glomerulonephritis during the first trimester of pregnancy. The edema occurred as early as the fifth week.…”
Section: Discussionmentioning
confidence: 99%
“…To date, anti-GBM disease occurring during gestation had only been reported in a few cases. [9][10][11][12][13][14][15][16][17][18] Patients with newly formed bilateral large corpus luteum cysts in patients with anti-GBM disease and pregnancy were not reported.…”
Section: Discussionmentioning
confidence: 99%